Extraction of protein concentrate from red bean (Phaseolus vulgaris L.): Antioxidant activity and inhibition of lipid peroxidation - Piñuel, Maria Lucrecia (2019)
Red Bean Protein Concentrate (RBPC) and their hydrolysates were used to evaluate the antioxidant capacity. The RBPC protein content was in the range of 57.38%-72.68% of the total sample content. RBPC protein profile showed a range of 15-100 kDa. Phaseolin protein was identified with bands of 45 and 50 kDa. Phaseolin protein was found in all the RBPC samples at the different pHs assayed. In the gastric digestion phase, bands from 60 to 100 kDa were totally hydrolyzed with pepsin. Phaseolin protein (45 and 50 kDa) presented resistance to gastric hydrolysis. All the RBPCs and gastrointestinal digest presented antioxidant activity using ferric-reducing antioxidant power (FRAP), 2,2-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS), oxygen radical absorbance capacity (ORAC), and thiobarbituric acid reactive substances using the in vitro and in vivo methods. RBPC at pH 7.0 presented a value of 95.80 μmoL TE/g of RBPC (FRAP); 257.12 μmoL TE/g of RBPC (ABTS), and 1960 μmoL TE/g of RBPC (ORAC). Duodenal digest of RBPC presented high antioxidant activity with 225.77 μmoL TE/g of digest (FRAP); 345.21 μmoL TE/g of digest (ABTS); and 3256 μmoL TE/g of digest (ORAC). Gastric and duodenal digest of RBPC were used to inhibit lipid peroxidation using the in vitro method presenting a value of 87.95% and 93.0%, respectively. When the in vivo method in zebrafish larvae was used, values were 79.03% and 86.76%, respectively. RBPCs showed no reactive oxygen species (ROS) inhibition. However, RBPCs with gastric and gastrointestinal digests, presented ROS inhibition, 75.30% for gastric digests and 66.40% for gastrointestinal digests.